Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1002/pola.1986.080240819
|View full text |Cite
|
Sign up to set email alerts
|

FT‐IR study of the stabilization reaction of polyacrylonitrile in the production of carbon fibers

Abstract: SynopsisThe stabilized fibers prepared by heating PAN and a PAN copolymer in air and under reduced pressure have been examined by IT-IH spectroscopy in order to determine their chemical structures. Three kinds of reactions, cyclization, dehydrogenation, and oxygen uptake are found to occur almost simultaneously in the stabilization process in air by digital difference spectrum method. The effect of the comonomer is confirmed to accelate the dehydrogenation reaction and also the formation of acridone ring in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(91 citation statements)
references
References 9 publications
4
86
0
Order By: Relevance
“…For 120 min, two shoulders appeared at 1710 and 1660 cm −1 (Figure 1(f)). Shimada and Takahagi reported that these shoulders are assigned to the free ketones in hydronaphthyridine rings and the conjugated ketones in acridone rings, resulting from the oxygen uptake reaction [9,10]. Furthermore, a new small band at 2200 cm −1 was observed with stabilized fibers.…”
Section: Ftir Analysis Of Stabilized Pan Fibersmentioning
confidence: 96%
“…For 120 min, two shoulders appeared at 1710 and 1660 cm −1 (Figure 1(f)). Shimada and Takahagi reported that these shoulders are assigned to the free ketones in hydronaphthyridine rings and the conjugated ketones in acridone rings, resulting from the oxygen uptake reaction [9,10]. Furthermore, a new small band at 2200 cm −1 was observed with stabilized fibers.…”
Section: Ftir Analysis Of Stabilized Pan Fibersmentioning
confidence: 96%
“…3, the cyclization of nitrile groups yields an imine structure, which then probably tautomerizes to an enamine structure [23]. Thus, the 1595cm -1 band has been generally assigned to the combination vibrations of C=N and C=C stretching, and NH in-plane bending [24]. The formation of the ladder structure by cyclization is meaningful for making carbon fiber from PAN precursor.…”
Section: Sample Codementioning
confidence: 99%
“…2b). The second step was around 260°C-450°C, during which the curves exhibited a sharp decline, mostly due to dehydrogenation [16,17]. After the formation of a stable ladder structure via cyclization, the PAN homopolymer and poly(AN-CA) copolymer showed higher levels of decomposition.…”
Section: Characterizationmentioning
confidence: 99%
“…1b), which shows two shoulders at 1718 and 1660 cm -1 , which were due to the oxygen uptake reactions. The first shoulder was assigned to C=O stretching vibrations of a free ketone; the second was assigned to stretching vibrations of a conjugated ketone [16,17]. In this work, the major difference between IA and CA when used as comonomers containing acid groups is the number of carboxylic groups, which provides more opportunities to induce the nitrile group to cyclize following the ionic mechanism.…”
Section: Characterizationmentioning
confidence: 99%